2003
DOI: 10.1007/s00170-003-1573-6
|View full text |Cite
|
Sign up to set email alerts
|

Social-technical aspects in modern manufacturing

Abstract: Manufacturing companies must compete on more and more global market. Continuos quality improvement, reduction of products' price and production series' shortening are necessary to be competitive. In such a situation development of production systems is necessary. It can be done only by development of all manufacturing systems' elements, like production methods, machines, process, control and information systems. An important part of manufacturing systems, very often not appreciated enough is human being. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
1
10
0
1
Order By: Relevance
“…Additionally, Shackel (1991) defined usability as ''in accordance with the functional characteristics of the human, the system easily and effectively used by specific user groups.'' Nielsen (Nielsen 1994) suggested that the product or system should meet a social and practical acceptability.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, Shackel (1991) defined usability as ''in accordance with the functional characteristics of the human, the system easily and effectively used by specific user groups.'' Nielsen (Nielsen 1994) suggested that the product or system should meet a social and practical acceptability.…”
Section: Introductionmentioning
confidence: 98%
“…Implementation of such kind of a system requires proper design of the communication process with human operators taking into account social-technical aspects and it influence on machine operators work [30,31].…”
Section: Demonstrator Of Multiagent Integrated Monitoring Systemmentioning
confidence: 99%
“…Operator ma bardzo znaczący wpływ na wynikową efektywność systemu, zależną od podejmowanych przez niego decyzji [10]. Zaangażowanie operatorów w proces przepływu informacji ma również duże znaczenie socjotechniczne wpływające na ich efektywność i zaangażowanie [11]. Budowany system ma on pełnić przede wszystkim rolę wsparcia dla operatorów co jest niewątpliwie zgodne z wynikami badań innych zespołów [12].…”
Section: Zintegrowany System Monitorowania Procesu Wytwarzaniaunclassified